2016
DOI: 10.3390/v8080220
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Ventral Horns and Lymphoid Organ Involvement in Powassan Virus Infection in a Mouse Model

Abstract: Powassan virus (POWV) belongs to the family Flaviviridae and is a member of the tick-borne encephalitis serogroup. Transmission of POWV from infected ticks to humans has been documented in the USA, Canada, and Russia, causing fatal encephalitis in 10% of human cases and significant neurological sequelae in survivors. We used C57BL/6 mice to investigate POWV infection and pathogenesis. After footpad inoculation, infected animals exhibited rapid disease progression and 100% mortality. Immunohistochemistry and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 54 publications
3
44
0
1
Order By: Relevance
“…In tissues where lesions were present, severity was scored on a scale of 0–4 with 0 indicating no lesions and 4 indicating severe lesions. Spleen, liver, kidney, heart, lymph node and intestine from the moribund HRTV-infected hamster and a sham-infected control were also processed for IHC following standard protocols (Hermance et al, 2016; Santos et al, 2016). The presence of HRTV antigen was detected in the fixed tissues using a mouse monoclonal antibody against the nucleoprotein (Calvert and Brault, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In tissues where lesions were present, severity was scored on a scale of 0–4 with 0 indicating no lesions and 4 indicating severe lesions. Spleen, liver, kidney, heart, lymph node and intestine from the moribund HRTV-infected hamster and a sham-infected control were also processed for IHC following standard protocols (Hermance et al, 2016; Santos et al, 2016). The presence of HRTV antigen was detected in the fixed tissues using a mouse monoclonal antibody against the nucleoprotein (Calvert and Brault, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…TBFVs can be divided into two groups based on their different tissue tropisms. Due to the high affinity of the virus for neural tissue, neurological disease manifestation is a characteristic pathogenetic scheme in TBEV, LIV, and POWV infections (70,(72)(73)(74)(75)(76). In contrast, KFDV, AHFV, and OHFV infections are typically associated with hemorrhagic manifestations, although neurotropism has been described for KFDV (68,(77)(78)(79)(80).…”
Section: Pathogenesismentioning
confidence: 99%
“…(), Pettersson & Fiz‐Palacios (), Proutski, Gould, & Holmes (), Santos et al. (), Smith et al. (), Thind & Price (), Whitney & Jamnback (), Zarnke & Yuill ().…”
Section: Resultsunclassified
“…Experimental studies on different species of mice reported the time between exposure and onset of symptoms to be between 2–6 days with an average survival time of 8 days (Hermance & Thangamani, ; Holbrook et al., ; Isachkova, Shestopalova, Frolova, & Reingold, ; Johnson, ; McLean & Donohue, ; Mlera, Meade‐White, Saturday et al, ; Santos, Hermance, Gelman, & Thangamani, ; Weiner, Cole, & Nathanson, ). Symptoms included ruffled fur, general malaise, weight loss, weak grip, hunched posture and limited mobility, which then progressed to neurological illness including meningoencephalitis and paralysis of the limbs (Hermance & Thangamani, ; Holbrook et al., ; Isachkova et al., ; Johnson, ; Khozinskaya, Chunikhin, Khozinsky, & Stefutkina, ; McLean & Donohue, ; Mlera, Meade‐White, Saturday, et al., ; Santos et al., ). One study reported an incubation period which varied from 3–4 to 3–8 days in relation to the age of the mice (Weiner et al., ).…”
Section: Resultsmentioning
confidence: 99%